Spontaneous healing response of oblique root fracture: case report with 4-year follow-up (Research, Society and Development, 2021)
Root fractures can involve the dentin, cementum, and pulp and commonly can occur as oblique fractures with varying orientations. The aim of this study was to demonstrate the maintenance of pulp health in a tooth with a fractured root without any endodontic treatment and to discuss the advantage of cone-bean computed tomography (CBCT) compared with traditional radiographs in the diagnosis of oblique root fractures. Intra-oral radiography of tooth 11 revealed a horizontal root fracture at the level of the apical third, while the sagittal CBCT slice reveals a complete fracture line running obliquely from the apical third on the buccal aspect through the cervical third on the palatal aspect.  Four years follow-up, the tooth has kept its pulp vitality, no tooth discoloration or discrepancy in arch position, without endodontic treatment. This result illustrates spontaneous healing of root fracture including preservation of pulp health. In addition, it confirms the importance of exams in 3 dimensions to correctly locate the fracture and assist in the treatment decision.